HUBUNGAN KECEPATAN LARI 40 METER DAN DAYA LEDAK OTOT TUNGKAI PADA ATLET ATLETIK PUTRI LANCANG KUNING CLUB - Mirda Yanti; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the author’s observation on the athletic athlete of Lancang Kuning club found problem in the long jump sport. That is at the prefix, run less fast and inconsistent running moves that cause doubt in taking repulsion and lack of repulsion when will make a leap. The purpose of this research is to determine the relationship speed of 40 meters running and explosive muscle limb power with long jumpt results on athletic athletic daughter Lancang Kuning club. The population in this research is the Lancang Kuning club Athletic athlete of 7 people. The sampling technique used is total sampling. The sample of this research is a female athlete who amounted to 7 people. Instrument in this research is speed running 40 meters, leg muscle power test by using standing broad jump and test long jump. This research used the product moment analysis. Based on the results of research and base processing, it can be concluded that for the relationship between variables X1,X2 with the variable Y obtamed by valuer r= 0,976 then rx1x2y > rtabel that is (= 0,976 > 0811) then Ha be accepted, in the other word there is a relationship, significantly between the running speed of 40 meters and with explosive power of the leg muscles with long. Jump results on the athletes athletic daughter Lancang Kuning club.Key word : Speed Run 40 Meters, Explosive Power Leg Muscle, Long Jump